Genome-wide analysis of the CaYABBY family in pepper and functional identification of CaYABBY5 in the regulation of floral determinacy and fruit morphogenesis - Ke Fang; Yi Liu; Zhiquan Wang; Xiang Zhang; Xuexiao Zou; Feng Liu; Zhongyi Wang (Journal of Integrative Agriculture, 2025)
Pepper fruit is highly favored for its spicy taste, diverse flavors, and significant nutritional benefits. The proper development of flowers and fruits directly determines the quality of pepper fruit. The YABBY gene family exhibits diverse functions in growth and development, which is crucial to the identity of flower organs. However, the specific functions of these genes in pepper remain unclear. In this study, nine CaYABBY genes were identified and characterized in pepper. Most CaYABBY genes were highly expressed in reproductive organs, albeit with varying expression patterns. The CaYABBY5 gene, uniquely expressed in petals and carpels, has been demonstrated to modulate floral organ determinacy and fruit shape through gene silencing in pepper and ectopic expression in tomato. Protein interaction analysis revealed an interacting protein SEPALLATA3-like protein (SEP3), exhibiting a similar expression profile to CaYABBY5. These findings suggest that CaYABBY5 may modulate the morphogenesis of floral organs and fruits by interacting with CaSEP3. This study provided valuable insights into the classification and function of CaYABBY genes in pepper.